Spatial pattern of woody plant species richness and composition in primary warm temperate evergreen forest in Kasugayama Hill, Japan - Shuntaro Watanabe; Yuri Maesako; Tomoya Inada (Scientific Reports)
Abstract Plant species richness and composition are influenced by complex interactions between biotic and abiotic factors that operate on different spatial scales. Since spatial scales vary continuously in nature, it is expected that multiple factors simultaneously affect species richness and composition at an intermediate spatial scale (i.e., the mesoscale landscape level). Previous studies have shown that local topography and elevation are important factors for shaping intermediate spatial scale plant species richness; however, the relative importance of these factors has rarely been examined. Here, we used spatially explicit woody plant data to examine the factors that characterize the spatial pattern of primary evergreen forest biodiversity at the intermediate spatial scale. We found that the spatial pattern of species diversity in a predominantly warm temperate evergreen forest at the landscape level is mainly characterized by shifts in species composition along the elevation gradient. Our study also found that compositional shift along the elevational gradient was mainly caused by habitat specialization among congeneric species, suggesting that niche partitioning among closely-related species is a fundamentally important feature of the intermediate spatial scale species richness pattern. Furthermore, we found that specialization in a habitat of closely-related species can be established even within a limited environmental gradient. This suggests that biotic interactions among closely-related species may be an important factor driving habitat specialization, and biotic interactions may play an important role in shaping landscape-scale biodiversity patterns.